Agrobacterium rhizogenes vs auxinic induction for in vitro rhizogenesis of Prosopis chilensis and Nothofagus alpina - Caro, Luis A. (2003)
The induction and improvement of in vitro rhizogenesis of microshoots of Prosopis chilensis (Mol.) Stuntz and Nothofagus alpina (Poep. et Endl. Oerst.) were compared using Agrobacterium rhizogenes (Ar) versus indole-3-butyric acid (IBA) in the culture media. Microshoots of P. chilensis (1-2 cm length), coming from in vitro grown seedlings, were cultivated in a modified Broadleaved Tree Medium (BTMm) containing half salt concentration of macronutrients and 0.05 mg.L-1 benzilaminopurine (BAP). After 30 days, microshoots with 2-4 leaves were selected and cultured in BTMm-agar in presence or abscense of Ar and in combination with IBA. For N. alpina, the apical shoots with the first 2 true leaves, from 5 weeks old seedlings, were cultured in the abovementioned medium, but with 0.15 mgL-1 of BAP. After 2 months, microshoots with 2-3 leaves were selected and cultured in BTMm-agar, supplemented with 5 mg.L-1 IBA or in liquid BTMm on perlite and, in the presence or absence of A. rhizogenes (Ar) and in combination with 3 mg.L-1 IBA. Rooting in P. chilensis reached 100.0% when Ar infection was produced in the presence of IBA, increasing both, the number and dry weight of roots. In N. alpina, 90.0% of rooting efficiency was obtained when Ar infection was produced in liquid culture and in the absence of auxin.